Fast Food Nation: The Dark Side of the All-American Meal - Haiven, Judy (Just Labour: A Canadian Journal of Work and Society, 2003)
Fast Food Nation: The Dark Side of the All-American Meal, by Eric Schlosser, is reviewed.